Modelling of carbon dioxide absorption into aqueous ammonia solution in a wetted wall column - Ghosh, U.; Hong, C.; Nandong, Jobrun; Shen, S. (Universiti Putra Malaysia, Universiti Pertanian Malaysia Press, 2015)
© 2015 Universiti Putra Malaysia Press. In this paper, a mathematical model is developed based on mass and momentum balance for carbon dioxide absorption into aqueous ammonia solution. The model is simplified based on the assumption that the CO2 absorption into aqueous ammonia is a pseudo-first-order reaction. Laplace transform method is applied in order to solve the partial differential model equation. Finally, the CO2 molar flux is expressedas a function of partial pressure of CO2, concentration of aqueous ammonia, temperature and gas-liquidcontact area. Variation of CO2 molar flux with partial pressure of CO2 and temperature is discussedand a comparison is performed with experimental data from literature. Variation of CO2 molar flux isalso shown with gas-liquid contact area. The calculated flux from the model follows the same trend asthat of the experimental data reported in literature and the accuracy is within the accepted limit. The mathematical model is very helpful to predict the CO2 molar flux as a function of partial pressure of CO2, concentration of aqueous ammonia, temperature and gas-liquid contact area.